2022
DOI: 10.1038/s41598-022-16887-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of milk thistle lipids to identify drought-tolerant genes

Abstract: Milk thistle is an oil and medicinal crop known as an alternative oil crop with a high level of unsaturated fatty acids, which makes it a favorable edible oil for use in food production. To evaluate the importance of Milk thistle lipids in drought tolerance, an experiment was performed in field conditions under three different water deficit levels (Field capacity (FC), 70% FC and 40% FC). After harvesting seeds of the plant, their oily and methanolic extracts were isolated, and subsequently, types and amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Various studies have shown that plants remodel lipid composition in response to drought (Gigon et al, 2004;Liu et al, 2021). In experiments on milk thistle, it was demonstrated that under drought conditions, PLA2-ALPHA (AT2G06925), which encodes a secretory phospholipase A2 enzyme, had reduced expression (Ghanbari Moheb Seraj et al, 2022), which is also evident in our results. Secreted PLA2s are low molecular weight calcium-dependent enzymes, which specifically hydrolyze the sn-2 position of phospholipids and can do that in an organized membrane (Mariani, Fidelio, 2019).…”
Section: Proteins Related To Lipid Metabolismsupporting
confidence: 86%
“…Various studies have shown that plants remodel lipid composition in response to drought (Gigon et al, 2004;Liu et al, 2021). In experiments on milk thistle, it was demonstrated that under drought conditions, PLA2-ALPHA (AT2G06925), which encodes a secretory phospholipase A2 enzyme, had reduced expression (Ghanbari Moheb Seraj et al, 2022), which is also evident in our results. Secreted PLA2s are low molecular weight calcium-dependent enzymes, which specifically hydrolyze the sn-2 position of phospholipids and can do that in an organized membrane (Mariani, Fidelio, 2019).…”
Section: Proteins Related To Lipid Metabolismsupporting
confidence: 86%
“…A meta-analysis was conducted to identify genes responsible for a wide range of abiotic stresses including drought, salinity, cold and high temperatures, alkali conditions, iron, aluminum, heavy metal toxicity, and nitrogen, phosphorus, and potassium deficiency. Plants change their transcriptome profile to endure unfavorable environmental conditions in response to different stresses 42 , 43 . Despite having a specific response to each stress in plants, this study indicates that there are a vast number of genes that are similarly expressed in response to different abiotic stresses, indicating that there is a core response system to all environmental stresses in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Biotic and abiotic stresses including drought affect the quality and yield of wheat, leading the research toward the understanding of the molecular mechanism of plant responses to stress 7 10 . Plants adopt different cellular responses including stomatal closure, activating transcription, changing the membrane stability, accumulating osmoprotectants and antioxidants, and scavenging reactive oxygen species (ROS) under drought stress 11 , 12 . These processes are regulated by the expression of different genes at the transcription level.…”
Section: Introductionmentioning
confidence: 99%